Sustained delivery of growth factors with high loading efficiency in a layer by layer assembly. (12th November 2019) - Damanik, Febriyani F. R.; Brunelli, Marzia; Pastorino, Laura; Ruggiero, Carmelina; van Blitterswijk, Clemens; Rotmans, Joris; Moroni, Lorenzo
Abstract : Layer by layer (LBL) assembly garnered considerable interest due to its ability to generate multifunctional films with high tunability and versatility in terms of substrates and polyelectrolytes, allowing the option to use complex devices and drugs. Abstract : Layer by layer (LBL) assembly has garnered considerable interest due to its ability to generate multifunctional films with high tunability and versatility in terms of substrates and polyelectrolytes, allowing the option to use complex devices and drugs. Polyelectrolytes, such as growth factors (GFs), are essential, but costly, delicate, biological molecules that have been used in various tissue regeneration applications. For this reason, the controlled drug delivery of efficiently loaded GFs via LBL assembly (GF-LBL) can contribute to the establishment of cost-effective biologically triggered biomedical applications. We have developed an LBL method to load GFs (specifically, transforming growth factor beta 1, platelet-derived growth factor ββ, and insulin growth factor 1), with up to 90% efficiency approximately, by gas plasma surface activation and tuning the pH to increase the ionic strength of polyelectrolytes. Poly(styrenesulfonate) (PSS) and poly(ethyleneimine) (PEI) have been used to provide the initial necessary charge for multilayer build-up. Heparin and dextran sulphate have been investigated as counter polyelectrolytes to enhance the activity of GFs by protecting their ligands, where heparin resulted in the highest achievable loading efficiency for all GFs. Oxygen gas plasma and acidic pH levels also resulted in a significant increase in GF loading efficiency. The three GFs were released by diffusion and erosion in a controlled manner over lengthy time scales and the bioactivity was maintained for up to 14 days. When tested as implants in vitro, GF-LBL constructs increased fibroblast proliferation, influenced cell morphology and migration, and enhanced myofibroblast differentiation, indicating that the biological functionalities of the GFs were preserved. In conclusion, this developed LBL assembly method can provide a simple drug delivery system, which may yield more effective applications for tissue regeneration as well as biomedical sciences at large.